Solvothermal synthesis and photocatalytic properties of ZnO micro/nanostructures. Issue 2 (1st February 2019) - Mao, Yuqin; Li, Yihuai; Zou, Yongjin; Shen, Xinying; Zhu, Luping; Liao, Guihong
Abstract: ZnO micro/nanostructures with different morphologies were prepared though a solvothermal process in the presence of surfactants. The structures and compositions were investigated using various techniques, including X-ray diffraction (XRD), a scanning electron microscope (SEM), a UV–vis spectrophotometer, and a fluorimeter. SEM observations revealed that the as-synthesized ZnO samples exhibited nanospheres (NSs), hexagonal disks (HDs), hexagonal bilayer disk-like structures (HBDs), and 3D flower-like hierarchitectures (HAs) due to the effect of the surfactant. XRD results showed that the prepared samples were wurtzite hexagonal phase ZnO with good crystallinity. The band gap energy ( E g ) values of the ZnO samples were 3.24 eV, 3.20 eV, 3.15 eV, and 3.24 eV for the ZnO NSs, HDs, HBDs, and 3D HAs, respectively. The photocatalytic properties of the as-synthesized samples were investigated by measuring the degradation on the Rhodamine-B (Rh-B). Among them, the as-synthesized 3D ZnO HAs had the highest photocatalytic activity, which showed a degradation efficiency of 97.34% for Rh-B under UV irradiation. The excellent photocatalytic efficiency is attributed to the hierarchical structures and good crystallinity, which led to the efficient separation of photogenerated electrons and holes.